Exploring enterprise system engineering skill gaps in the labor markets of Egypt and Tunisia - Mahmoud, Tariq; Gómez, Jorge Marx; El Alfy, Shahira (Business, Management and Economics Engineering, 2014)
The proposed research is driven by an existing need to develop a master programme in enterprise system engineering (ESE) to the Arab Universities. The main objective of the project is to ensure the development of a top-notch curriculum that comprises the latest technology and teaching methods while integrating the local labour market needs of the target countries. To achieve that, a labour market analysis in the ESE domain is conducted in this proposed research. The study is divided into two main parts, one is qualitative to uncover several issues in the labour markets of the target Arab countries relevant to ESE and the second part is quantitative designed to measure the skill gaps prevalent in those countries to which the master programme is exported. Besides the business problem calling for this research, its importance is leveraged by the strong evidence in the literature showing that supply and demand skills rarely match. This research is expected to explore and measure potential gaps between employment and education in ESE, a point that is crucial for more efficient education and employment in the Arab countries.